1998
DOI: 10.1037/0003-066x.53.11.1209
|View full text |Cite
|
Sign up to set email alerts
|

Psychological influences on surgical recovery: Perspectives from psychoneuroimmunology.

Abstract: Greater fear or distress prior to surgery is associated with a slower and more complicated postoperative recovery. Although anxiety presumably interferes with recuperation through both behavioral and physiological mechanisms, the pathways have been unclear. Recent work in psychoneuroimmunology (PNI) has demonstrated that stress delays wound healing. In addition, a second line of research has illustrated the adverse effects of pain on endocrine and immune function. A biobehavioral model is described that is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
254
0
13

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 486 publications
(291 citation statements)
references
References 91 publications
10
254
0
13
Order By: Relevance
“…In agreement with these laboratory findings, several studies have shown that greater fear or distress prior to surgery is associated with poorer outcomes including longer hospital stays, more postoperative complications, and higher rates of rehospitalization 34 .…”
Section: Stress and Wound Healingsupporting
confidence: 58%
“…In agreement with these laboratory findings, several studies have shown that greater fear or distress prior to surgery is associated with poorer outcomes including longer hospital stays, more postoperative complications, and higher rates of rehospitalization 34 .…”
Section: Stress and Wound Healingsupporting
confidence: 58%
“…The inclusion of comparable role-play strategies may limit the adverse effects of pain on endocrine and immune function on skin wound healing (Kiecolt- Glaser et al, 1998). Also caregivers may benefit from training protocols using role-play strategies targeting self-enhancement and positive emotions related to the social meaningfulness of the work they do.…”
Section: Discussionmentioning
confidence: 99%
“…Also caregivers may benefit from training protocols using role-play strategies targeting self-enhancement and positive emotions related to the social meaningfulness of the work they do. This may reduce their short and long term risk of health deterioration (Kiecolt-Glaser et al, 1998;Glaser and Kiecolt-Glaser, 2005;Tosevski and Milovancevic, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has indicated that the presence of elevated psychological symptoms may complicate treatment and may alter outcome [24,25,27,32,42,56]. That is not to say that those with a mental health diagnosis should not be considered for elective limb lengthening and reconstruction surgery.…”
Section: Background and Rationalementioning
confidence: 99%
“…Rather, all patients Table 8. Recommendations for preoperative evaluation [5,11,17,24,25,27,37,42,46,48,49] should be screened for the presence of psychiatric symptoms and appropriate management of these symptoms should be required before planning surgical intervention of this magnitude (Table 8). As the lead team member, the surgeon should be aware of the patient's preexisting mental health condition and the potential impact during treatment.…”
Section: Background and Rationalementioning
confidence: 99%